Distinctive germline expression of class I human leukocyte antigen (HLA) alleles and DRB1 heterozygosis predict the outcome of patients with non-small cell lung cancer receiving PD-1/PD-L1 immune checkpoint blockade. Issue 1 (17th June 2020) - Correale, Pierpaolo; Saladino, Rita Emilena; Giannarelli, Diana; Giannicola, Rocco; Agostino, Rita; Staropoli, Nicoletta; Strangio, Alessandra; Del Giudice, Teresa; Nardone, Valerio; Altomonte, Maria; Pastina, Pierpaolo; Tini, Paolo; et al.
Abstract : Background: Nivolumab is a human monoclonal antibody against programmed cell death receptor-1 (PD-1) able to rescue quiescent tumor infiltrating cytotoxic T lymphocytes (CTLs) restoring their ability to kill target cells expressing specific tumor antigen-derived epitope peptides bound to homologue human leukocyte antigen (HLA) molecules. Nivolumab is currently an active but expensive therapeutic agent for metastatic non-small cell lung cancer (mNSCLC), producing, in some cases, immune-related adverse events (irAEs). At the present, no reliable biomarkers have been validated to predict either treatment response or adverse events in treated patients. Methods: We performed a retrospective multi-institutional analysis including 119 patients with mNSCLC who received PD-1 blockade since November 2015 to investigate the predictive role of germinal class I HLA and DRB1 genotype. We investigated the correlation among patients' outcome and irAEs frequency with specific HLA A, B, C and DRB1 alleles by reverse sequence-specific oligonucleotide (SSO) DNA typing. Results: A poor outcome in patients negative for the expression of two most frequent HLA-A alleles was detected (HLA: HLA-A*01 and or A*02; progression-free survival (PFS): 7.5 (2.8 to 12.2) vs 15.9 (0 to 39.2) months, p=0.01). In particular, HLA-A*01-positive patients showed a prolonged PFS of 22.6 (10.2 to 35.0) and overall survival (OS) of 30.8 (7.7 to 53.9) months, respectively. We also reported that HLA-A and DRB1 locus heterozygosis (het) were correlated to a worse OS if we considered het in the locus A; in reverse, long survival was correlated to het in DRB1. Conclusions: This study demonstrate that class I and II HLA allele characterization to define tumor immunogenicity has relevant implications in predicting nivolumab efficacy in mNSCLC and provide the rationale for further prospective trials of cancer immunotherapy.